Examining the Effects of Postmastectomy Radiation Therapy in Prepectoral Versus Subpectoral Autologous Breast Reconstruction. Issue 3 (May 2021) - Patel, Ashraf A.; Arquette, Connor P.; Yesantharao, Pooja S.; Borrelli, Mimi R.; Broderick, Kristen P.; Cheesborough, Jennifer E.; Lee, Gordon K.; Nazerali, Rahim S.
Abstract : Background: Postmastectomy radiation therapy (PMRT) is known to increase the risk of multiple adverse outcomes after breast reconstruction. In the context of delayed-immediate autologous breast reconstruction, PMRT is typically conducted after placement of subpectoral (SP) tissue expanders. With the re-emergence of prepectoral (PP) reconstruction, there are little data assessing the outcomes of PP reconstruction in breasts receiving PMRT. We compared postoperative outcomes of PMRT patients undergoing delayed-immediate, autologous breast reconstruction with placement of tissue expanders in either the PP or SP plane. Methods: A retrospective chart review was conducted on all consecutive patients who underwent delayed-immediate autologous breast reconstruction and received PMRT at either the Stanford University or the Johns Hopkins University Hospitals between January 2009 and December 2018. Demographics, comorbidities, perioperative information, and oncologic data were collected for all patients. Complications were collected and analyzed after stage 1 surgery, between 30 days of stage 1 and up to stage 2 surgery, and after stage 2 surgery. Multivariable regressions were used to determine predictors of 1 or more complications. Results: A total of 71 patients (73 breasts) were included. Prepectoral reconstruction comprised of 52.2% of the cohort, and the remaining 47.8% were SP reconstructions. Demographics and comorbidities were similar between groups, except for premastectomy radiation, which was more prevalent in the PP cohort ( P = 0.010). Complications were similar between cohorts after stage 1 surgery ( P = 0.420), between stages 1 and 2 ( P = 0.100), and after stage 2 ( P = 0.570). There were higher rates of skin necrosis in the SP cohort between stages 1 and 2 (PP: 2.6%, SP: 20%, P = 0.004). Multivariable analysis revealed body mass index to be the only predictor of complication ( P = 0.041). The mean number of revisionary surgeries was higher in the SP cohort (PP: 0.8 vs SP: 1.9, P = 0.002). The mean follow-up was 385.5 days and similar between groups ( P = 0.870). Conclusions: Rates of overall complication were similar between PP and SP expander placement. However, in SP reconstructions, skin necrosis was significantly higher between stages 1 and 2. The patients in the SP cohort also underwent a greater number of revisionary surgeries, although overall rates of pursuing any revisionary surgery were similar between groups.